(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This work tries to explore the arrangements of TQM practices in two unique parts and recognizes an arrangement of normal TQM practices appropriate to both the segments, by assessing the writing on TQM practices took after by Manufacturing and management ventures. The procedure embraced was a review of distributed research examines Manufacturing and management enterprises were chosen and their TQM practices were thought about. The research found that statistically significant positive correlations exist between employee engagement and TQM. This is indicative that, the more engaged employees are, the more satisfied they will be with their job, and vice versa.